Grammatical Errors Found in Articles' Abstracts of Indonesian Scholarly Journals - Wulandari, Indra (JEELS (Journal of English Education and Linguistics Studies), 2014)
This study is aimed to know the grammatical errors found in the articles’ abstracts of scholarly journals published by one of Indonesian Islamic State Colleges in 2008-2010. The theory used to analyze the data in this case study is Burt and Kiparsky’s theory, namely Surface Strategy Taxonomy. This theory devides errors into errors of omission,errors of addition, errors of misformation and errors of misordering. This results of the study show that there are 172 items of grammatical errors. The most frequent type of grammatical error is omission with the total number is 72 items or 41.9%. The second is errors of misformation which consist of 57 items or 33.1%. The next is errors of addition (27 items or 15.7%) and finally is errors of misordering as the least number of errors with 16 items or 9.3%.